Study of the mechanism of digitalization boosting urban low-carbon transformation - Xinfa, Tang; Jinglin, Li (Frontiers in Environmental Science, 2022)
Today's world climate problem is severe, urban climate is bad, to deal with a series of climate problems, low-carbon measures are essential. Digital development is becoming a new driving force for social development, and the development of urban low-carbon transformation should be based on digital construction. On the basis of exploring the relationship between digitalization and urban low-carbon transformation, this paper focuses on the practical application and theoretical mechanism of digitalization in urban low-carbon transformation. Finally, from the perspective of carbon neutralization, this paper puts forward some reference strategies for reducing carbon emissions and realizing sustainable urban development in China.